NGO's and the United Nations - Martens, K. author. aut Link
XV, 199 p.
Keywords: NGOs and the United Nations reveals how NGOs have changed their interaction with the UN since the mid-1990s. It also looks at how their representation to the UN, their consultative status and their characteristic features influence their relationship with the UN. The case studies include some of the most renowned players on the international scene, such as Amnesty International, Human Rights Watch, CARE International and Oxfam International.